1997
DOI: 10.1080/03601239709373107
|View full text |Cite
|
Sign up to set email alerts
|

Acetochlor - a comparative study on parameters governing the potential for water pollution

Abstract: The leaching behaviour of the herbicide acetochlor [2-chloro-N-(2-ethyl-6-methylphenyl)-N-(ethoxymethyl)acetamide] was determined as compared with two congener compounds, alachlor [2-chloro-N-(2,6-diethylphenyl)-N-(methoxymethyl)acetamide] and metolachlor [2-chloro-N-(2-ethyl-6-methylphenyl)-N-(2-methoxy-1-methylethyl)acetamid e]. The leaching profiles of the herbicides in columns with different types of soil and their capacity factors in reverse phase HPLC were compared. An approach for preliminary characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 8 publications
0
6
0
2
Order By: Relevance
“…Koplin et al (2) have reported that acetochlor was detected in 29% of the rain samples from four sites from Iowa, 17% from the stream samples from 51 sites across 9 states, and 0% of the groundwater samples from 38 wells across 8 states. Acetochlor is classified as a leacher in soil, and its potential for contamination of groundwater is comparable with those of alachlor and metolachlor (3). The mobility of pesticides in soil is one of the principal parameters controlling the extent to which they may represent a risk for groundwater contamination (4).…”
Section: Introductionmentioning
confidence: 99%
“…Koplin et al (2) have reported that acetochlor was detected in 29% of the rain samples from four sites from Iowa, 17% from the stream samples from 51 sites across 9 states, and 0% of the groundwater samples from 38 wells across 8 states. Acetochlor is classified as a leacher in soil, and its potential for contamination of groundwater is comparable with those of alachlor and metolachlor (3). The mobility of pesticides in soil is one of the principal parameters controlling the extent to which they may represent a risk for groundwater contamination (4).…”
Section: Introductionmentioning
confidence: 99%
“…Even throughout the world, only a little data is available for acetochlor sorption (Kholodov et al 2005;Lengyel and Földényi 2003;Liu et al 2000;Wang et al 1999;Zheng and Ye 2002) and very little for its desorption (Taylor et al 2004). Previous studies based on soil column and sorption experiments have shown that acetochlor presents a risk of groundwater contamination (Balinova 1997;Zheng and Ye 2002), consistent with its frequent presence observed in groundwater (Barbash et al 2001;Kolpin et al 1996Kolpin et al , 1998. Existing data indicates that the sorption capacity of soils for acetochlor increases with increasing content of soil organic carbon, whereas other soil characteristics are less important (Kholodov et al 2005;Wang et al 1999).…”
mentioning
confidence: 96%
“…Soil sorption influences pesticide vapourization, bioavailability, degradation and leaching, and hence it ultimately determines pesticide fate in the environment (Balinova 1997;Laabs et al 2000Laabs et al , 2002Ye 2003;Yu et al 2006). Therefore, the first step in understanding the environmental fate of a pesticide is to study its sorption characteristics.…”
mentioning
confidence: 99%
“…Weber and Peter (1982), studying adsorption on seven different soils using radiolabeled molecules, found that acetochlor was more sorbed than metolachlor [2‐chloro‐6′‐ethyl‐ N ‐(2‐methoxy‐1‐methylethyl)‐ o ‐acetoluidide] or alachlor [2‐chloro‐2′,6′‐diethyl‐ N ‐(methoxymethyl) acetanilide], and concluded that acetochlor is less mobile than the other two chloroacetanilides. Balinova (1997), however, using percolation experiments on soil columns, showed that acetochlor, like the other chloroacetanilides (metolachlor and alachlor), is a potential ground water contaminant. Zheng and Ye (2002) also concluded, based on adsorption and thin‐layer chromatography experiments, that acetochlor presents a risk of ground water contamination, particularly in sandy soil or if aquifers are shallow.…”
mentioning
confidence: 99%